[N′-(5-Bromo-2-oxidobenzylidene-κO)-2-chlorobenzohydrazidato-κ2N′,O](methanol-κO)(methanolato-κO)oxidovanadium(V) - Fu-Ming Wang (Acta Crystallographica Section E, 2011)
The VV atom in the title complex, [V(C14H8BrClN2O2)(CH3O)O(CH3OH)], is six-coordinated by one phenolate O, one imine N and one enolic O atom of the hydrazone ligand, one oxide O atom, one methanol O atom and one methoxide O atom in a distorted octahedral geometry. The dihedral angle between the two benzene rings of the hydrazone ligand is 13.2 (3)°. The deviation of the V atom towards the oxide O atom from the plane defined by the three donor atoms of the hydrazone ligand and the methoxy O atom is 0.318 (2) Å. Bond lengths are comparable with those observed in similar oxidovanadium(V) complexes with hydrazone ligands. In the crystal, pairs of molecules are linked through intermolecular O—H...N hydrogen bonds, forming dimers.